A tributação na perspectiva do Estado neoliberal: leitura da obra Law, legislation and liberty, de Friedrich August von Hayek - Tuma, Eduardo (2010)
In the years that have widened the contradictions of the capitalist system - 1974 - Friedrich August von Hayek wrote a memorable thesis of Law, Legislation and Liberty target of analysis in this study. Spontaneous order, freedom and minimal state intervention in society: these are expressions that represent the essence of the author's thinking, which proposes a constitutional model as opposed to socialist ideas. Until today, the ideas found in reading the work of Friedrich August von Hayek have particular importance, because it proposes concepts to ensure the functioning of the state, especially with regard to the need for fixing the burden distributed to individuals, which requires a total control of public spending. It can not be denied that the work, published more than three decades ago, survives and serves as a stimulus to the State that aims to achieve the so-called fair taxation without neglecting the maintenance of spontaneous order as a necessity for the preservation of the free economy